2013
DOI: 10.4069/kjwhn.2013.19.2.119
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Life Style, Menstrual Attitude and Premenstrual Syndrome in Nursing Students

Abstract: Purpose:The purpose of this study was to identify the relationships between life style, menstrual attitude and premenstrual syndrome in nursing students. Methods: The study participants were 246 nursing students of a university in Gyeunggi province. Data were collected by a self-administered questionnaire from May to June, 2012. Collected data were analyzed using the SPSS/WIN 20.0 program with descriptive statistics, Pearson correlation coefficient, t-test, one-way ANOVA and Scheffe test. Results: Students who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 13 publications
1
11
0
2
Order By: Relevance
“…또한 월 경태도는 월경 불편감 정도에 영향을 받아 월경전증후군 이 있는 경우 월경 태도에 대한 부정적인 영향을 미치는 것으로 보고되었다 [13]. 그 외 대상자 특성으로 월경관련 특성 [14], 식생활 습관 [15,16] …”
unclassified
“…또한 월 경태도는 월경 불편감 정도에 영향을 받아 월경전증후군 이 있는 경우 월경 태도에 대한 부정적인 영향을 미치는 것으로 보고되었다 [13]. 그 외 대상자 특성으로 월경관련 특성 [14], 식생활 습관 [15,16] …”
unclassified
“…Some have shown that alcohol consumption increases the incidence and severity of PMS and dysmenorrhea [25][26][27][28]. At present, the study of Nybergetal et al [29] may explain the relationship between the two in terms of hormones, they found that a dose of alcohol affected the serum concentrations of allopregnanolone throughout the menstrual cycle, which might affect the occurrence of severe premenstrual syndrome and dysmenorrhea.…”
Section: Discussionmentioning
confidence: 91%
“…Depressed mood, affective lability, irritability and impaired concentration were symptoms that had higher scores across the age groups. Table 2 shows the severity of Premenstrual symptoms in the age groups graded as minimal (0-10), mild (11)(12)(13)(14)(15)(16)(17)(18)(19)(20), moderate (21-30) and severe (31-40). None of the participants reported minimal symptoms.…”
Section: Resultsmentioning
confidence: 99%